A critical need for the concept of matrescence in perinatal psychiatry - Athan, Aurelie M. (Frontiers in Psychiatry, 2024)
The concept of matrescence, akin to adolescence but for mothers, has gained increasing attention in perinatal psychiatry, marking a paradigm shift towards understanding the holistic development of mothers. Matrescence encompasses the myriad psychological, social, cultural, and existential changes that occur as women transition into motherhood. Despite advances in maternal mental health, a bias towards pathologizing maternal experiences persists in research and practice. This perspective advocates for the integration of matrescence into perinatal psychiatry, drawing from the work of Dana Raphael and contemporary scholarship. Matrescence offers a strengths-based framework that acknowledges both the challenges and opportunities of motherhood, emphasizing the normative aspects of a mother's self-development. By adopting matrescence terminology and nosology, clinicians and researchers can enhance traditional psychiatric classifications. Additionally, matrescence underscores the importance of considering ecological systems and historical factors in maternal well-being, highlighting the need for comprehensive and compassionate healthcare services. Embracing matrescence as a fundamental concept in perinatal psychiatry holds promise for improving maternal mental health outcomes and promoting the flourishing of mothers worldwide.